Educational implications derived from the Saudi national anthem and its role in the consolidation of the national identity from the viewpoint of General Education Teachers - Alkhayyat, Alia Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aims at devising the educational contents of the Saudi national anthem and its role in consolidating the national identity, highlighting the role of the educational contents derived from the Saudi national anthem in establishing the national identity. And, to find out if there are statistically significant differences between the responses of the sample of 307 male and female teachers from different cities in Saudi Araba, to determine the role of educational content derived from the national anthem in the consolidation of national identity, which can be attributed to variables: (sex - educational stage - educational qualification - the number of years of experience). The researcher used the deductive and descriptive analytical method. Moreover, the study concluded the most important results: The consolidation of the educational contents of the Saudi national anthem through three aspects: cognitive, emotional, and political competence represented in the behavior of the individual towards the country. Furthermore, by focusing on the study data-surveying, it has been found that the phrase (the national anthem is important for young and old citizens) is ranked first and to a very large extent. Then, the phrase (The words of the national anthem are clear and understandable to students) is ranked second. On the other hand, the phrase (The meanings of the anthem were discussed with the students) It has an average score and a penultimate rank. While the phrase (the National Day is just a holiday) is ranked as the last place. The study recommended the importance of preserving the values of citizenship and focusing on rights and duties through curricular and extracurricular activities. As well as, the preservation of the Arabic language. In fact, this task-directed to the media of education in general and the schools. Working toward connecting the children with the Islamic religion and Islamic civilization and to be pride in heroes and pioneers.